2010
DOI: 10.1080/01635581.2010.516869
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Chemopreventive Potential of Luteolin-7-O-Glucoside Isolated From Ophiorrhiza mungos Linn

Abstract: The anticarcinogenic potential of the phytocompound Luteolin-7-O-Glucoside (LUT7G), isolated from the leaves of Ophiorrhiza mungos Linn, was studied against 4 different cancer cell lines (COLO 320 DM, AGS, MCF-7, and A549) and normal VERO cell line. The ability of LUT7G to induce apoptosis was determined by its antiradical activity, DNA fragmentation, expression of β-catenin, and chemopreventive efficacy in vivo by administering rats with DMH (20 mg/kg b.w., s.c.) for 4 consecutive wk and supplementing with 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 27 publications
0
48
0
1
Order By: Relevance
“…Luteolin also shown that; it inhibits the expression of cyclin D1, a downstream target of wnt/β-catenin pathway (Pandurangan et al, 2013a). Baskar et al, (2011) reported that luteolin-7-O-glucoside isolated from ophiorrhizamungos Linn showed to decrease the expression of β-catenin in COLO 320 DM cells.…”
Section: Luteolin Effects On the Wnt-β-catenin Pathwaymentioning
confidence: 99%
“…Luteolin also shown that; it inhibits the expression of cyclin D1, a downstream target of wnt/β-catenin pathway (Pandurangan et al, 2013a). Baskar et al, (2011) reported that luteolin-7-O-glucoside isolated from ophiorrhizamungos Linn showed to decrease the expression of β-catenin in COLO 320 DM cells.…”
Section: Luteolin Effects On the Wnt-β-catenin Pathwaymentioning
confidence: 99%
“…In regards to the effect of DMH metabolite produced by CYP450 on beta-catenin gene expression [15,16,18,19], the data of this research together with our previous results [34,35] imply that feeding of rats with caraway essential oils and powder could modulate the enzymes interfere with DMH metabolism (GST and CYP1A1) leading to the decreased level of β-catenin gene expression. These entire events, finally leaded to the decreased level of ACF formation terminating in decreased progression of colon…”
Section: Discussionmentioning
confidence: 85%
“…A plant extract of Eleutherine palmifolia led to a significant decrease in the level of nuclear beta-catenin protein, resulted in the inhibitory effect on the transcription of TCF/beta-catenin in SW480 colon cancer cells in a dose-dependent manner together with selective cytotoxicity against three colorectal cancer cell lines [48]. Luteolin-7-O-Glucoside induced apoptosis by scavenging ROS and suppressing the expression of β-catenin in COLO 320 DM cells and effectively inhibited ACF development in DMH-induced experimental carcinogenesis [15]. Silibinin supplementation to DMH-treated rats restored the levels of GSH-dependent enzymes and decreased the levels of β-catenin, PCNA, argyrophilic nucleolar organizer regions and cyclin D1 [49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Luteoloside, a natural flavone subclass derived from plants, has exhibited a series of biological activities, such as potential antibacterial and antifungal [4], free radical scavenging [5], anti-oxidative capabilities [6,7], protection effects against doxorubicininduced cardiotoxicity [8], and anticarcinogenic potential against colon carcinogenesis [5] and hepatocellular carcinoma [9,10], etc. However, the effects of luteoloside on blood malignancy have not been reported.…”
Section: Introductionmentioning
confidence: 99%